2021
DOI: 10.1029/2020wr027514
|View full text |Cite
|
Sign up to set email alerts
|

Fill‐and‐Spill: A Process Description of Runoff Generation at the Scale of the Beholder

Abstract: The famous French mathematician Henri Poincaré said that "Science is built up of facts, as a house is with stones. But a collection of facts is no more a science than a heap of stones is a house" (Poincaré, 1902). Our perceptual understanding of runoff processes sometimes appears as a heap of facts (or observations), with many of them dating back to the First International Hydrological Decade and the following years, when key observations were made regarding translatory flow (Hewlett & Hibbert, 1967), saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 133 publications
(181 reference statements)
2
40
0
1
Order By: Relevance
“…It is reasonable and practical to conceptualize subsurface flow dynamics as the two‐state integral‐balance between saturated and unsaturated storage (Duffy, 1996), though the subsurface flow can be much more complex due to heterogeneity of landscape, soil, and hydrogeological environments (McDonnell et al, 2021; Somers & McKenzie, 2020). The PIHM simulated saturated storage dynamics was validated by only streamflow but also water tables at three different locations, which increased our confidence in capturing the percentage of streamflow attributable to groundwater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable and practical to conceptualize subsurface flow dynamics as the two‐state integral‐balance between saturated and unsaturated storage (Duffy, 1996), though the subsurface flow can be much more complex due to heterogeneity of landscape, soil, and hydrogeological environments (McDonnell et al, 2021; Somers & McKenzie, 2020). The PIHM simulated saturated storage dynamics was validated by only streamflow but also water tables at three different locations, which increased our confidence in capturing the percentage of streamflow attributable to groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…much more complex due to heterogeneity of landscape, soil, and hydrogeological environments(McDonnell et al, 2021;Somers & McKenzie, 2020). The PIHM simulated saturated storage dynamics was validated by only streamflow but also water tables at three different locations, which increased our confidence in capturing the per-centage of streamflow attributable to groundwater.…”
mentioning
confidence: 86%
“…Although the landscape structure and associated runoff generation mechanisms of low‐gradient, tile‐drained IMLs differs from that of steep, bedrock hillslopes, the conceptual filling and spilling of landscape storages and resultant threshold runoff behavior are similar. Further, fill‐and‐spill was recently proposed as a framework to more broadly describe runoff generation processes by which landscape storages become progressively filled and connected (McDonnell et al., 2021). Another comparable bottom‐up mechanism explaining threshold runoff response in untiled, minimally managed hillslopes is “transmissivity feedback” (Bishop, 1991; Kendall et al., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a linear storage‐discharge relationship is a classic approach found and accepted in the literature (De Rooij, 2013; Ebrahim & Villholth, 2016; Fenicia et al, 2006). However, many studies have shown that basin temporal variations in the hydrological process such as evapotranspiration that may actively compete with subsurface drainage for the same water resource that supplies streamflow (Shaw & Riha, 2012; Tashie et al, 2019) and the water‐level elevation could be responsible for accelerating the exfiltration of pre‐event water into the river bed due to the fill and spill process (Mcdonnell et al, 2021; Wittenberg, 1999) or increase the stream network density (Godsey & Kirchner, 2014), could help to explain the exponential best fit for the storage increases. GRACE's mission ended in 2017 and it provided the 16 years of data used in this study; however, the continuity of the monitoring was guaranteed from the launched mission GRACE Follow‐On (GRACE‐FO) in 2018 (Frappart & Ramillien, 2018).…”
Section: Discussionmentioning
confidence: 99%